2014
DOI: 10.1080/23273798.2014.892144
|View full text |Cite
|
Sign up to set email alerts
|

‘hotdog’, not ‘hot’ ‘dog’: the phonological planning of compound words

Abstract: Do we say dog when we say hotdog? In five experiments using the implicit priming paradigm, we assessed whether nominal compounds composed of two free morphemes like sawdust or fishbowl are prepared for production at the segmental level in the same way that two-syllable monomorphemic words (e.g. bandit) are, or instead as sequences of separable words (e.g. full bowl or grey dust). The experiments demonstrated that nominal compounds are planned as a single sequence, not as two sequences. Specifically, the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
1
22
1
1
Order By: Relevance
“…They also argued that whole-word representations are stored at the lexeme level since the lack of the critical interaction effect in the picture verification task rules out conceptual and lemma stages while the lack of the interaction in repetition rules out post-lexical stages. However, this result was not replicated in a study of unimpaired Dutch speakers, who produced both plural-dominant and singular-dominant plurals more slowly than singulars, and plural-dominant plurals more Downloaded by [New York University] A c c e p t e d M a n u s c r i p t A MORPHOLOGICALLY RICH LEXICON 10 slowly than singular dominant plurals (Baayen, Levelt, Schreuder, & Ernestus, 2008) Turning now to post-lexical stages, Jacobs and Dell (2014) utilized the implicit priming/form preparation paradigm to tap into segmental processing, a stage that is commonly referred to as phonological encoding. In their study, compounds such as sawdust showed priming effects that were similar to monomorphemic words (e.g., bandit) but that differed from noun phrases (e.g., grey dust).…”
Section: The Cognitive Architecture Of Spoken Productionmentioning
confidence: 95%
“…They also argued that whole-word representations are stored at the lexeme level since the lack of the critical interaction effect in the picture verification task rules out conceptual and lemma stages while the lack of the interaction in repetition rules out post-lexical stages. However, this result was not replicated in a study of unimpaired Dutch speakers, who produced both plural-dominant and singular-dominant plurals more slowly than singulars, and plural-dominant plurals more Downloaded by [New York University] A c c e p t e d M a n u s c r i p t A MORPHOLOGICALLY RICH LEXICON 10 slowly than singular dominant plurals (Baayen, Levelt, Schreuder, & Ernestus, 2008) Turning now to post-lexical stages, Jacobs and Dell (2014) utilized the implicit priming/form preparation paradigm to tap into segmental processing, a stage that is commonly referred to as phonological encoding. In their study, compounds such as sawdust showed priming effects that were similar to monomorphemic words (e.g., bandit) but that differed from noun phrases (e.g., grey dust).…”
Section: The Cognitive Architecture Of Spoken Productionmentioning
confidence: 95%
“…Most data that test such predictions come from comprehension studies, or from studies on the interface between comprehension and production, presenting complex words as distractors to pictures with monomorphemic names (e.g., Zwitserlood et al, 2002; Köster and Schiller, 2008; Lüttmann et al, 2011b; Verdonschot et al, 2012). To date, studies on the actual production of complex words are quite rare (e.g., Roelofs and Baayen, 2002; Lüttmann et al, 2011a; Jacobs and Dell, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…For instance, Levelt et al (1999) proposed that frequent compounds are represented as single units at the lemma level and in terms of individual morphemes at word-form level (see also Bien, Levelt, & Baayen, 2005;Jacobs & Dell, 2014). Other authors have proposed stored representations of compounds at the level of word forms (Caramazza, 1997;Janssen, Bi, & Caramazza, 2008).…”
Section: Accounting For Phrase Frequency Effectsmentioning
confidence: 99%